The spleen-liver axis supports obesity-induced systemic and fatty liver inflammation via MDSC and NKT cell enrichment - Brummer, Christina; Singer, Katrin; Renner, Kathrin; Bruss, Christina; Hellerbrand, Claus; Dorn, Christoph; Reichelt-Wurm, Simone; Gronwald, Wolfram; Pukrop, Tobias; Herr, Wolfgang; Banas, Miriam; Kreutz, Marina (Molecular and Cellular Endocrinology, 2025)
Obesity promotes adipose tissue inflammation and leads to impaired local but also systemic immune cell homeostasis. This chronic low-grade inflammation plays a significant role in the development of obesity-associated secondary diseases such as metabolic associated fatty liver disease or cancer. The spleen as the central organ of immune cell regulation is anatomically directly connected to the visceral adipose tissue and the liver via the portal vein circulation. However, the inter-organ crosstalk and linkage between obesity-induced systemic, hepatic and splenic immune cell dysregulation is not clearly outlined. In this study blood, spleen, and liver immune cells of non-obese wildtype vs. leptin deficient obese BTBR mice were isolated and analyzed in terms of leukocyte composition by flow cytometry. Significant differences between circulating, spleen- and liver-resident immune cell distribution revealed, that obesity-induced hepatic and systemic immune cell dysregulation is distinct from splenic immune cell reprogramming. Fatty liver inflammation was associated with splenic myeloid derived suppressor cell (MDSC) and natural killer T cell (NKT) enrichment whereas loss of hepatic T and B cells was not reflected by the splenic lymphocyte landscape. Correlation analysis confirmed a selective strong positive correlation between spleen and liver MDSC and NKT cell distribution indicating that the spleen-liver axis modulates obesity-induced immune dysregulation in a cell-specific manner. Similar results were observed in a diet-induced obesity mouse model. These data provide novel insights into the role of the spleen-liver axis in obesity-induced inflammation and foster the understanding of obesity-associated complications such as fatty liver disease and cancer.
CRIS-Team Scopus Importer:2025-03-21
Keywords: Myeloid-derived suppressor cells; Natural killer cells; Obesity; Spleen-liver-axis; T cell dysregulation